(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The study is dedicated to analyzing the treatment outcomes of 153 children with cystic echinococcosis of the liver at the Specialized Pediatric Surgical Clinic of Samarkand State Medical University (2006–2017). The patients were divided into a control group (2006–2011, n=82) and a main group (2012–2017, n=71) to compare traditional and modern surgical methods. The main group was treated using topical minilaparotomy, cyst processing with 80% glycerol, low-frequency ultrasound cavitation, express diagnostics, and albendazole chemoprophylaxis. This approach eliminated postoperative complications (0% vs. 12.2% in the control group), halved blood loss, and prevented recurrences over a 15-year follow-up period. The results confirm the high efficacy of the proposed approach in pediatric surgery.